The effect of high volume power training on repeated high-intensity performance and the assessment of repeat power ability: A systematic review - Natera, A. O.; Cardinale, M.; Keogh, J. W. L. (Sports Medicine, 2020)
Background: High volume power training (HVPT) involves high volumes of high-velocity resistance training, with the aim to improve repeated high-intensity efforts (RHIEs). Repeat power ability (RPA) is the ability to repeatedly produce maximal or near maximal efforts. Assessments of RPA using external loading may determine the ability to perform repeat RHIEs typical of many sports and, therefore, provide useful information on the effectiveness of training. Objectives: (1) Identify the different HVPT protocols; (2) examine the acute responses and chronic adaptations to different HVPT protocols; (3) identify different lower body RPA assessment protocols and highlight similarities, differences and potential limitations between each protocol, and; (4) describe the reliability and validity of RPA assessments. Methods: An electronic search was performed using SPORTDiscus, PubMed, CINAHL and Embase for studies utilising HVPT protocols and assessments of RPA. Eligible studies included peer-reviewed journal articles published in English. Results: Twenty studies met the inclusion criteria of the final review. Of the eight longitudinal studies, three were rated as fair and five were rated as poor methodological quality, respectively. In contrast, all 12 cross-sectional studies were considered to have a low risk of bias. Preliminary evidence suggests that HVPT can enhance RHIE, RPA, anaerobic capacity, anaerobic power and aerobic performance. HVPT generally consists of 2-3 sessions per week, utilising loads of 30-40% 1 repetition maximum (RM), for 3-5 sets of 10-20 repetitions, with inter-set rest periods of 2-3 min. RPA assessments can be valid and reliable and may provide useful information on an athlete`s ability to perform RHIE and the success of HVPT programmes. Conclusions: HVPT can be used to improve a number of physical qualities including RPA and RHIE; while a variety of RPA assessments provide valid and reliable information regarding the athlete`s ability to perform RHIEs. Considering the heterogeneity in the HVPT protocols currently used and the relatively low volume and quality of longitudinal publications in this area, further studies are needed to identify the effects of a variety of HVPT methods on RPA, RHIE and other performance outcomes and to identify the most valid and reliable RPA outcomes to use in such studies.